COMPREHENSIVE ANALYSIS ON APPROACHES EMPLOYED IN DEALING WITH POSTNATAL DEPRESSION - 1Hussam Atiah Ali Domari, 2Anwar Mohammed Suwayhan, 3Abdulrahman Falah Almutairi, 4Asrar Sayar Alenezi, 5Reem Ibrahim Shatty Alshammari, 6ALanood Mohammed Alalati, 7Mohammed AbdulrhmanAlshayiqi, 8Mouna Huwaykim Hulayyil Alanazi (Chelonian Research Foundation, 2022)
Postnatal depression (PND) poses a significant mental health challenge for new mothers globally. This article comprehensively surveys different procedures utilized to address PND, including counting solutions, psychotherapy, and elective medicines. This study utilized an efficient survey and assessment strategy to investigate information and highlight the qualities and shortcomings of each mediation. The results show the contrasts within the execution of these models through pictures, words, and charts. The discourse digs into the treatment results and advocates a multidisciplinary approach that meets people's needs. The findings highlight the need for individualized, collaborative endeavors to combat PND and empower advanced investigation to refine mediations and progress outcomes. Keywords: postnatal depression, interventions, pharmacological therapy, psychotherapy, alternative therapies, systematic review, meta-analysis. Depression